AB0042 High expression of s100 calgranulins genes in peripheral blood mononuclear cells of patients with takayasu arteritis. (15th June 2017) - Kabeerdoss, J; Goel, R; Mohan, H; Danda, D
Abstract : Background: Takayasu arteritis (TA) is inflammatory disorder that affects aorta and its branches. Toll-like receptors (TLR) 1 to 4 are highly expressed in aorta (1). Activation of TLR4 causes transmural arteritis in human temporal artery–SCID chimera model (2). Ligand responsible for TLR4 activation is not known in TA. Objectives: Aim of the study is to examine the expression of TLR4 and its endogenous ligands in peripheral blood mononuclear cells (PBMCs) of patient with TA. Methods: RNA from PBMCs of 24 TA patients and 19 sex and age matched healthy controls were extracted. The mRNA expression of various endogenous TLR4 ligands, TLR4, RAGE, interleukin-6 (IL-6) and IL-8 were quantified in real time PCR using specific primers and SYBR Green qPCR master mix. Serum S100A8/A9 and S100A12 levels were measured using commercial ELISA kits. S100A8/A9 and S100A12 were measured in cell culture supernatant of un-stimulated and lipopolysaccharides (LPS) stimulated PBMCs, cultured for 4 hours. t-test was used to compare between the groups. P<0.05 was considered as statistically significant. Results: The mRNA of S100A8, S100A9, S100A12 and TLR4 were highly expressed in TA as compared to healthy controls, while RAGE, HSP70 and IL-6 had lower expression in TA. No difference in serum levels of S100A8/A9 and S100A12 was noted between TA and healthy controls. LPS induced high secretion of both S100A8/A9 and S100A12 levels in both TA and healthy controls (Figure-1). However, the stimulatory response in healthy controls [2.88 (1.7–3.53) fold] was significantly higher as compared to TA [1.345 (1–1.82) fold; p<0.05] as measured by delta S100A12 (LPS/unstimulated control). Numerically delta S100A8/A9 was also higher in healthy controls [2.04 (1.7–5.6) fold] as compared to TA [1.38 (1.09–3.6) fold; p=0.129]. Conclusions: mRNA expression of S100A8, S100A9, S100A12 and TLR4 in PBMCs of TA patients were higher as compared to healthy controls. Despite this, S100A12 secretion was lower in TA as compared to healthy controls upon LPS challenge. References: Pryshchep O, Ma-Krupa W, Younge BR, et al (2008) Vessel-specific Toll-like receptor profiles in human medium and large arteries. Circulation 118:1276–1284. Deng J, Ma-Krupa W, Gewirtz AT, et al (2009) TLR4 and TLR5 induce distinct types of vasculitis. Circ Res 104:488–495. Acknowledgements: This study was funded by grants-in-aid from Science and Engineering Research Board (SERB), Department of Science and Technology (DST), Government of India under young investigator scheme to JK (SB/YS/LS-14/2014). Disclosure of Interest: None declared